The law against itself. A discussion with Massimo La Torre - Amaya, Amalia; Bonifaz, Leticia; Cerdio, Jorge; La Torre, Massimo; Mora-Sifuentes, Francisco M. (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2020)
This contribution is a dialogue among different legal philosophers about “Il Diritto Contro se Stesso. Saggio sul Positivismo Giuridico e la sua Crisi”, the latest book of Professor Massimo La Torre. Taking the work of this author, the participants reflected and argued on central topics for the theory and philosophy of law: What is the nature of law? Is legal reasoning eminently moral reasoning? What is the place that legal practice should occupy in the conceptualization of law? What place does force occupy in the law?
Keywords: nature of law; legal positivism; legal reasoning; legal ethics